2023
DOI: 10.1021/acsomega.3c00383
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Flexible Electrodes for P-Type (Nickel Oxide) Dye-Sensitized Solar Cell Performance Based on the Cellulose Nanofiber Film

Abstract: The preparation of flexible electrode, including working electrode (WE) and counter electrode (CE), for dye-sensitized solar cells (DSSCs) utilizing metal oxides using environmentally friendly sustainable TEMPO-oxidized cellulose nanofibers (TOCNFs) is reported in this work. A new type of flexible electrode for the DSSCs, which were made of cellulose nanofiber composites with nickel hydroxide [CNF/Ni(OH) 2 ] substrate films and cellulose nanofiber composites with polypyrrole (CNF/PPY). Nickel hydroxide, Ni(OH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…NiO, which has a band gap of 3.6 eV, is generally used as a photocathode in DSSCs. 263,264 Zannotti et al introduced rGO to enhance the performances of NiO NPs formed by the sol–gel process. 265 The rGO coated on the surface of NiO through the thermal reduction of GO not only increased the surface area and mesopore volume but also contributed to the improvement of electron transport.…”
Section: Applications Of Nanoporous Oxide Electrodesmentioning
confidence: 99%
“…NiO, which has a band gap of 3.6 eV, is generally used as a photocathode in DSSCs. 263,264 Zannotti et al introduced rGO to enhance the performances of NiO NPs formed by the sol–gel process. 265 The rGO coated on the surface of NiO through the thermal reduction of GO not only increased the surface area and mesopore volume but also contributed to the improvement of electron transport.…”
Section: Applications Of Nanoporous Oxide Electrodesmentioning
confidence: 99%
“…The use of this process for nanoparticle production offers several advantages, including shorter production times and lower operating temperatures compared to alternative methods. [24] The effect of annealing, ZnO NPs generated using the sol-gel technique was reported by Omri et al [25] To investigate the formation of ZnO nanostructures, Kumar et al [26] employed a sol-gel method involving zinc sulfate heptahydrate and NaOH as precursors. It was found that the bandgap of ZnO nanostructures can be lowered by increasing the calcination temperature, which in turn causes the maximum absorption to move to longer wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical materials of carbon compounds having the size smaller than 10 nm are known as carbon dots (C-dots). These materials have special properties including chemiluminescence, photoluminescence, photoinduced electron transfer, and electrochemical luminescence. , C-dots find potential applications in bioimaging, , biosensing, , chemical sensing, and biomedicine . C-dots are the nanomaterials considered as potential candidates in the application of bioimaging, both in vitro and in vivo, and for diagnosis purposes, due to their unique fluorescent nature and having excellent biocompatibility, less cytotoxicity, and better solubility in water. In this work, C-dots were synthesized from citric acid (CA) and o -phenylenediamine ( o -OPD). The synthesized C-dots and presynthesized nickel oxide nanoparticles were used as precursors for the synthesis of nickel oxide composites of C-dot nanomaterials.…”
Section: Introductionmentioning
confidence: 99%